Oral hygiene practices and habits among dental students and staff in a dental college, India. - Ch Saikiran; K Jyothirmai; N Saimadhavi; R Lavanya; R Sudhakara Reddy; Lavanya R Reddy; T Ramesh; Padma M Reddy (Cumhuriyet University, 2014)
Introduction: Oral health is an essential component of general health in one's life. Oral self practices are very effective in keeping up one's good oral health from an individual's point of view. Such hygienic conditions prevent many oral diseases from happening or control them from damaging oral health adversely. Aim: To investigate the oral hygiene practices and habits among dental students and staff in a dental college. Materials and methods:  A survey with the aid of specially designed questionnaire was made anonymously, in order to assess the oral health behaviour among these people. Results: A number of 425 dental students as well as faculty members was investigated. Only 34.9% of students and faculty members are following oral self health habits strictly.    It was also observed that the staff members were very much concerned about oral hygiene rather than students were. Conclusion: The results show that dental students need a lot of awareness in their oral self hygiene.  Awareness programmes  must be conducted frequently to boost up the oral self hygiene practices among them for many good reasons.